2020
DOI: 10.3389/fimmu.2020.577823
|View full text |Cite
|
Sign up to set email alerts
|

MPL Adjuvant Contains Competitive Antagonists of Human TLR4

Abstract: Monophosphoryl lipid A (MPL ®) is the first non-alum vaccine adjuvant to achieve widespread clinical and market acceptance, a remarkable achievement given that it is manufactured from a Salmonella enterica endotoxin. To understand how MPL ® successfully balanced the dual mandate of vaccine design-low reactogenicity with high efficacy-clinical-and research-grade MPL was evaluated in human and mouse cell systems. Stimulatory dose response curves revealed that most preparations of MPL are much more active in mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…This might be attributed to the significantly higher cytokine levels of IL-23, IL-12p70, and TNFα when stimulating with MPL-s or LPS compared to MPL-SM. Along this line, Wang et al recently demonstrated that various research-grade Salmonella enterica –derived MPLA preparations purchased from different companies showed varying efficacy on TLR4 stimulation and TNFα secretion in human THP-1 cells, whereas mouse RAW264.7 cells responded similarly to these compounds ( 44 ). The phenomenon of TLR-induced, antigen-independent lymphocyte expansion has been described before but has gained little interest in vaccine development so far.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the significantly higher cytokine levels of IL-23, IL-12p70, and TNFα when stimulating with MPL-s or LPS compared to MPL-SM. Along this line, Wang et al recently demonstrated that various research-grade Salmonella enterica –derived MPLA preparations purchased from different companies showed varying efficacy on TLR4 stimulation and TNFα secretion in human THP-1 cells, whereas mouse RAW264.7 cells responded similarly to these compounds ( 44 ). The phenomenon of TLR-induced, antigen-independent lymphocyte expansion has been described before but has gained little interest in vaccine development so far.…”
Section: Discussionmentioning
confidence: 99%
“…MPL, a TLR4 agonist, is a detoxified lipopolysaccharide (LPS), which has been proved to be an effective adjuvant in several studies [ 19 ]. Poly I:C is a synthetic double-stranded (ds) RNA, a mimic of viral dsRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid A is usually diphosphorylated (82). Edgar Ribi observed that monophosphorylated lipid A is significantly less immunogenic (83), and since then, monophosphoryl lipid A (MPL) has been FDA-approved as an adjuvant (84). A promising strategy to create OMVs consisting of monophosphorylated lipid A is to express the Helicobacter pylori Hp0021 gene in the OMVproducing organism.…”
Section: Engineering To Decrease Lps Toxicitymentioning
confidence: 99%